Natural disaster experience does not affect environmental attitudes or prosociality: Evidence from the 2021 flood in Germany - Nils Christian Hönow; Kiran Karki; Maximilian N. Burger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
In July 2021, severe floods devastated parts of Germany, causing numerous casualties and extensive damage to property and infrastructure. As climate change is expected to increase the frequency and severity of such extreme weather events, understanding their social implications is crucial. Using data from three nationwide surveys, we examine the impact of the 2021 flood on environmental attitudes, pro-environmental behaviors, and the support for climate-related policies across a wide range of indicators. Results reveal no statistically significant effects, regardless of the estimation methods or measures of flood exposure used. We additionally investigate the flood's effect on prosociality, assessed through measures such as past charitable donations and incentivized decisions in a dictator game. Similarly, we find only limited variation in prosociality, but with impacts differing based on whether respondents in affected areas also sustained damage to their households. These findings challenge the expectation that direct exposure to natural disasters increases environmental awareness and prosocial behavior. – – Im Juli 2021 verwüsteten schwere Überschwemmungen Teile Deutschlands, führten zu zahlreichen Todesopfern und verursachten erhebliche Schäden an Eigentum und Infrastruktur. Da der Klimawandel voraussichtlich die Häufigkeit und Intensität solcher extremen Wetterereignisse erhöhen wird, ist es wichtig, ihre gesellschaftlichen Auswirkungen zu verstehen. Anhand von Daten aus drei landesweiten Umfragen untersuchen wir die Auswirkungen der Flut von 2021 auf Umweltbewusstsein, umweltfreundliches Verhalten und die Unterstützung klimabezogener Politiken anhand einer Vielzahl von Indikatoren. Die Ergebnisse zeigen keine statistisch signifikanten Effekte - unabhängig von den verwendeten Schätzmethoden oder den Messgrößen zur Hochwasserexposition. Darüber hinaus analysieren wir den Einfluss der Flut auf prosoziales Verhalten, gemessen anhand von Spendenaktivitäten sowie Entscheidungen in einem experimentellen "Dictator Game". Auch hier zeigen sich nur geringe Unterschiede im prosozialen Verhalten, wobei die Auswirkungen davon abhängen, ob Befragte in den betroffenen Gebieten auch Schäden an ihrem Haushalt erlitten haben. Diese Ergebnisse stellen die Annahme in Frage, dass das direkte Erleben von Naturkatastrophen Umweltbewusstsein und prosoziales Verhalten erhöht.
Keywords: D64; D91; Q54; Q58; 330; Natural disaster; flood; environmental awareness; environmental attitudes; environmental behavior; climate policy; prosociality